Optimasi Perolehan dan Karakterisasi Serbuk Mucilago Hibiscus rosa-sinensis L. (MHR) sebagai Binder Tablet - Imam Prabowo; Iqbal Julian Rianda Pradana Putra; Via Rifkia (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
This study aims to optimize the yield of MHR powder because the research conducted by Shah and Patel in 2010 was still very small, namely around 8%. Optimization was carried out by varying the soaking and heating times and then characterizing the MHR powder to test whether the MHR powder was a good candidate as a tablet binder. Characterization tests performed were organoleptic tests, particle size distribution, polysaccharide identification, swelling ratio, solubility, flow properties, viscosity, and water content. The most optimal MHR powder recovery was 1 hour of soaking time and 6 hours of heating time with a yield of 11.50 ± 1.40%. The results of the characterization of the MHR powder included: organoleptic test of the MHR powder was light brown, had a distinctive herbal odor and was tasteless, the particle size distribution test was in the range of 100-400 microns with the highest percentage of particles in the size of 186 μm, the swelling ratio was at 23 .47 ± 0.41, positive polysaccharide identification test, solubility was at 0.000426 ± 0.000034, viscosity was at 4520 ± 1224.42. Broadly speaking, MHR powder is a potential candidate as a tablet binder, that was proved from tablet formulation using MHR powder as binder resulted hardness, friability and disintegration time as well as formulation that using Avicel PH102 as binder.